The new tax credit regime for digital games production in Ireland - O'Brien, Maria (Irish Journal of Arts Management and Cultural Policy, 2024)
Tax credit and incentive regimes for creative production are increasingly a feature of the production landscape in many jurisdictions. Historically, Ireland has provided significant opportunities for both international and national audiovisual production, including through the provision of a generous tax credit regime of up to 32% of eligible expenditure for film and TV production. However, the digital games/videogames sector has not been considered as part of the audiovisual industries but as forming part of the Information and Communications Technology (ICT) sector. Until now. The recent introduction of a digital games tax credit in Ireland has, in part at least, framed the digital games sector as part of the cultural and creative industries, given the need for European Commission approval for the tax credit as a cultural state aid under EU Treaty provisions. This article addresses the impact of the contested framing of the digital games sector as simultaneously part of the industrial and cultural industries. It does so through interrogation of framing of games as both industrial and cultural in both EU state aid and Irish taxation policy.